2011
DOI: 10.5465/amj.2011.60263089
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cutting Ties, Organizational Density, and New Firm Formation in the U.S. Biotech Industry, 1994–98

Abstract: The present paper examines the role of cooperative relations among incumbents in the formation of new firms. We argue that cooperative interfirm relations that bridge geographically remote and diverse sources of knowledge, i.e., cross-cutting ties, contribute to new firm formation. Employing data on state-level entries in the US biotech industry from 1994 to 1998, we find support to the following hypotheses: the formation of new firms in a focal region of an industry is positively related to the number of cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 71 publications
0
25
0
1
Order By: Relevance
“…Knowledge brokerage is derived from the theory of structural holes, which states that certain firms or individuals play a key role in bridging knowledge gaps and generating access among previously unconnected knowledge resources (Burt, 1992). It has been found that brokers who are familiar with activities in different regions/countries are better able to see how knowledge or practices in one region could create value in the other and then translate the knowledge or practices into business opportunities in the target region (Bae, Wezel, & Koo, 2011;Burt, 2004). In particular, knowledge brokers have advantages in accessing valuable information prior to others, and they enjoy benefits in terms of exerting controls over rewarding opportunities, which are referred to as information and control benefits (Burt, 1992).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge brokerage is derived from the theory of structural holes, which states that certain firms or individuals play a key role in bridging knowledge gaps and generating access among previously unconnected knowledge resources (Burt, 1992). It has been found that brokers who are familiar with activities in different regions/countries are better able to see how knowledge or practices in one region could create value in the other and then translate the knowledge or practices into business opportunities in the target region (Bae, Wezel, & Koo, 2011;Burt, 2004). In particular, knowledge brokers have advantages in accessing valuable information prior to others, and they enjoy benefits in terms of exerting controls over rewarding opportunities, which are referred to as information and control benefits (Burt, 1992).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…It has been found that individuals who span different countries are more likely to identify opportunities via timely access to non-redundant information (Ellis, 2011). For example, R&D collaborations between distant geographic areas give rise to the establishment of new firms due to access to novel and diverse knowledge (Bae et al, 2011). Because the source of entrepreneurial opportunities is rooted in information asymmetries (Eckhardt & Shane, 2003), returnee knowledge brokers have advantages in pursuing entrepreneurial opportunities due to better access to a broad array of novel and non-redundant ideas by spanning countries (Burt, 2004;Ellis, 2011).…”
Section: International Knowledge Brokerage and Returnee Entrepreneurshipmentioning
confidence: 99%
“…At the same time, it is recognized that the success of such initiatives not only depends on the existence of adequate venture support programmes to facilitate the creation of NTBFs, but also on the ability of entrepreneurs themselves to persist and endure in the face of numerous challenges (Markman et al, 2005;Stoltz, 1997). Scholars (Bae et al, 2011;Bruyat and Julien, 2001) have observed that technology entrepreneurs typically face challenges that are characterized by uncertainty, ambiguity, scarcity of resources, marginal performance and information asymmetry, among other technology-specific issues. Thus, founders of NTBFs often find themselves in particularly complex and challenging situations.…”
Section: Introductionmentioning
confidence: 99%
“…Ties to other organizations play an important role in these outcomes because they act as conduits of valuable 'network resources' (Dyer and Singh, 1998;Gulati, 1999Gulati, , 2007Podolny and Page, 1998). The pattern of firms' inter-organizational relations affects their market actions and, more broadly, the processes of competition in a market (e.g., Bae et al, 2011;Baker, 1990;Burt, [1992Burt, [ ] 2009Uzzi, 1997;Zaheer et al, 2000). Firms that lack cooperative relations are disadvantaged compared with those embedded in them.…”
Section: Network Ties and Uncertainty Reductionmentioning
confidence: 99%